Effect of Microencapsulation on Chemical Composition and Antimicrobial, Antioxidant and Cytotoxic Properties of Lemongrass (Cymbopogon flexuosus) Essential Oil - Anely Maciel de Melo; Rafaela Cristina Turola Barbi; Francisco Lucas Chaves Almeida; Weysser Felipe Cândido de Souza; Atacy Maciel de Melo Cavalcante; Hugo Junior Barboza de Souza; Diego Alvarenga Botrel; Soraia Vilela Borges; Roberto Germano Costa; Max Rocha Quirino; Solange de Sousa (Food Technology and Biotechnology, 2022)
Research background. Lemongrass (Cymbopogon flexuosus) essential oil exhibits antimicrobial and antioxidant properties due to the presence of α-citral and β-citral. Essential oils are susceptible to volatilization and oxidation when applied to food matrices. Therefore, a barrier is needed to protect this material. The present study aims to produce microparticles containing lemongrass essential oil, with gum arabic and maltodextrin using spray drying technology. Experimental approach. Lemongrass essential oil was extracted by the hydrodistillation method and later microencapsulated with different wall materials. Free and microencapsulated lemongrass essential oil was evaluated for the cytotoxic activity (using Artemia salina as test sample), chemical composition (GC-MS), encapsulation efficiency, antioxidant activity (DPPH, ABTS and FRAP), antimicrobial activity and minimum inhibitory concentration. Results and conclusions. The lethal concentration (LC50) of lemongrass essential oil in the cytotoxic test was 8.43 μg/mL against Artemia salina; a high activity that can be associated with the presence of α-citral (~33%) and β-citral (~21%) in the samples, since these were the main compounds with bioactive properties. The highest value of microencapsulation efficiency (88.11%) was obtained when only gum arabic was used as wall material. In general, the microparticles showed satisfactory antioxidant activity (expressed as Trolox equivalents, between 348.66 and 2042.30 µmol/100 g) and bactericidal effect in vitro against Gram-positive and Gram-negative microorganisms. In conclusion, the microencapsulated lemongrass essential oil is a promising functional additive in the food and pharmaceutical industries. Novelty and scientific contribution. This study shows that microparticles containing lemongrass essential oil can be prepared using gum arabic and maltodextrin as wall materials by spray drying, resulting in high microencapsulation efficiency. The drying process maintained the antimicrobial and antioxidant properties of the essential oil. Therefore, the microencapsulated lemongrass essential oil is considered a natural, functional and promising additive in the food industry. Its antimicrobial action can increase the shelf life of fresh and semi-fresh products such as cheese, yogurts and meat products. In addition, its antioxidant action can delay the lipid and protein oxidation in food products.